Involvement of an ATP-dependent carboxylase in a CO2-dependent pathway of acetone metabolism by Xanthobacter strain Py2. - Sluis, M K (1996)
The metabolism of acetone by the aerobic bacterium Xanthobacter strain Py2 was investigated. Cell suspensions of Xanthobacter strain Py2 grown with propylene or glucose as carbon sources were unable to metabolize acetone. The addition of acetone to cultures grown with propylene or glucose resulted in a time-dependent increase in acetone-degrading activity. The degradation of acetone by these cultures was prevented by the addition of rifampin and chloramphenicol, demonstrating that new protein synthesis was required for the induction of acetone-degrading activity. In vivo and in vitro studies of acetone-grown Xanthobacter strain Py2 revealed a CO2-dependent pathway of acetone metabolism for this bacterium. The depletion of CO2 from cultures grown with acetone, but not glucose or n-propanol, prevented bacterial growth. The degradation of acetone by whole-cell suspensions of acetone-grown cells was stimulated by the addition of CO2 and was prevented by the depletion of CO2. The degradation of acetone by acetone-grown cell suspensions supported the fixation of 14CO2 into acid-stable products, while the degradation of glucose or beta-hydroxybutyrate did not. Cultures grown with acetone in a nitrogen-deficient medium supplemented with NaH13CO3 specifically incorporated 13C-label into the C-1 (major labeled position) and C-3 (minor labeled position) carbon atoms of the endogenous storage compound poly-beta-hydroxybutyrate. Cell extracts prepared from acetone-grown cells catalyzed the CO2- and ATP-dependent carboxylation of acetone to form acetoacetate as a stoichiometric product. ADP or AMP were incapable of supporting acetone carboxylation in cell extracts. The sustained carboxylation of acetone in cell extracts required the addition of an ATP-regenerating system consisting of phosphocreatine and creatine kinase, suggesting that the carboxylation of acetone is coupled to ATP hydrolysis. Together, these studies provide the first demonstration of a CO2-dependent pathway of acetone metabolism for a strictly aerobic bacterium and provide direct evidence for the involvement of an ATP-dependent carboxylase in bacterial acetone metabolism.